2019
DOI: 10.1016/j.forsciint.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based survey of the distribution volume of ethanol: Comparison of empirically determined values with anthropometric measures

Abstract: Blood-alcohol calculations are often required in forensic science casework, they commonly used the Widmark equation.  Anthropometric equations can tailor Widmark's rho-factor for a given individual.  Results using anthropometric equations were in reasonably good agreement with rho-factors determined empirically.  A regression equation involving the person's age, height and body weight was the best model for male subjects.  Consideration of the person's BMI gave more accurate results for females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…For a water soluble drug like ethanol, its distribution volume ( V d ) is influenced by a person's age and gender, with lower values observed in women and in elderly men. Table makes a comparison of ethanol V d determined for healthy male and female subjects in controlled drinking experiments (Maskell et al, ). The average V d was 0.69 L/kg for men compared with 0.60 L/kg for women, which suggests that after drinking the same dose/kg of ethanol females achieve a roughly 15% higher peak BAC than males.…”
Section: Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a water soluble drug like ethanol, its distribution volume ( V d ) is influenced by a person's age and gender, with lower values observed in women and in elderly men. Table makes a comparison of ethanol V d determined for healthy male and female subjects in controlled drinking experiments (Maskell et al, ). The average V d was 0.69 L/kg for men compared with 0.60 L/kg for women, which suggests that after drinking the same dose/kg of ethanol females achieve a roughly 15% higher peak BAC than males.…”
Section: Absorptionmentioning
confidence: 99%
“…The Widmark‐rho‐factor and the person's BMI are negatively correlated as shown in a drinking study in people with widely different BMI (Maudens et al, ). A recent evidence‐based survey of the distribution volumes of ethanol reported average values of 0.69 L/kg for men and 0.60 L/kg for women as shown in Table (Maskell et al, ). In any individual case, the rho‐factor might vary by a factor of two in the population of drinkers.…”
Section: Pharmacokinetic Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will give a better estimate of V d than the average (mean) V d across a population (from where previous estimates of the uncertainty of V d were taken). Recent work has demonstrated that the most accurate equations to estimate the V d of an individual are that of Watson, Watson, and Batt for males and Forrest for females (13).…”
Section: Figmentioning
confidence: 99%
“…Gender‐related difference in body composition mean that after drinking the same dose of ethanol per kg body weight, a woman's BAC is 10–15% higher and thus a correspondingly greater effect on impairment. The higher BAC in women is accounted for by their smaller volume of distribution for ethanol, being on average 0.60 L/kg compared with 0.70 L/kg in males (Maskell, Jones, Savage, & Scott‐Ham, ).…”
Section: Alcoholic Beveragesmentioning
confidence: 99%